Foreign political and economical interests of Ukraine in India: establishment, present condition and prospects - Rachek, Dmytro V. (Проблеми міжнародних відносин, 2011)
The article considers the chronology of relations between Ukraine and India from
the early 90-ies till today. Main achievements of relations in political and economic
directions are being analyzed; periods of downturn and activity in relations are being
investigated. В данной статье рассматривается хронология отношений между Украиной
и Индией от начала 90-ых до сегодня. Анализируются основные достижения
отношений в политическом и экономическом направлениях, исследуются
периоды спада и активности отношений.